Home and family as a mirror of the country past: review of the book by D. I. Petin «The History of the Omsk clan of Batyushkin» - A. V. Antoshin (Омский научный вестник: Серия "Общество. История. Современность")
The analytical review is devoted to a new and conceptual microhistorical research — the monograph «The History of the Omsk clan of Batyushkin», published by the Omsk historian-archivist and local historian, PhD in History, Associate professor Dmitry Igorevich Petin. From the standpoint of a problematic vision, the substantive aspects of the book are highlighted, which, in the opinion of the reviewer, are worthy of close attention of the academic community, as well as plots, the discussion of which can be continued in a debatable manner. In conclusion, the high significance of the analyzed monograph for understanding the Modern History of Russia is emphasized.